Analisis Kepercayaan Diri Remaja Melalui Pola Komunikasi Orang Tua Tunggal - Yuningsih, Sri Endin; Rahmasari, Gartika (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
A family exists because of a marriage consisting of a father, mother and other members. Every individual has a dream of a harmonious family. But in reality, not every family has a harmonious family. The cause of family disharmony occurs due to separation, whether due to divorce or the death of one of the parents. Separation due to divorce or death can have an impact on family communication patterns, especially with children in their teens. The family plays an important role in forming self-confidence in adolescents. Self-confidence in teenagers who come from disharmonious families tend to have low self-confidence (selfesteem). This research aims to find out how much influence parents' communication patterns have on teenagers' self-confidence. The method in this research uses a quantitative descriptive method by collecting data obtained from distributing questionnaires to teenagers aged 18-21 years who have single parents in Cipadung Village, Cibiru District with a sample size of 240. Using the Slovin formula with Likert scale measurements. The results of this research show that the communication pattern developed by single parents is an authoritative (democratic) communication pattern. The relationship between communication patterns and adolescent self-confidence has a significant and positive relationship so that single parent communication patterns influence adolescent self-confidence.